Observer-Based Quadrature Signal Generator for UPQC in a Single-Phase Distribution System - Pradeep Kandukuri; Kumar K. Vinay (ITM Web of Conferences, 2022)
This paper presents a control algorithm for generation of reference voltage and current based on Observerbased QSG (Quadrature Signal Generator) for UPQC (Unified Power Quality Conditioner) in a Single-Phase Distribution System. The proposed UPQC is a combination of DSTATCOM and DVR used for load and source compensation such as voltage sag and swell, voltage and current harmonics etc. The proposed control algorithm is capable of generating reference signals from the distorted voltages and currents. In this paper, an improved OQSGbased PLL (Phase-Locked Loop) is utilized over OQSG to enable and operate with increased bandwidths that will improve the dynamic response, tracking accuracy and faster detection of reference signal under all varying load and grid conditions. The control algorithm is tested and evaluated using MATLAB / Simulink.